2008
DOI: 10.1111/j.1582-4934.2008.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin‐1: an ambiguous partner in cell signalling and cancer

Abstract: Caveolae are small plasma membrane invaginations that have been implicated in a variety of functions including transcytosis, potocytosis and cholesterol transport and signal transduction. The major protein component of this compartment is a family of proteins called caveolins. Experimental data obtained in knockout mice have provided unequivocal evidence for a requirement of caveolins to generate morphologically detectable caveolae structures. However, expression of caveolins is not sufficient per seto assure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
160
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(169 citation statements)
references
References 223 publications
(346 reference statements)
8
160
0
1
Order By: Relevance
“…presence of the protein is associated with more aggressive tumor behavior. For additional information in this respect, the interested reader may wish to consider previous reviews where such ideas have been discussed extensively [11,61]. A corollary to this concept is that Caveolin-1 function as a tumor suppressor is linked to events favoring cell death, while more aggressive tumor behavior is likely to be associated with Caveolin-1-dependent mechanisms that favor cell survival.…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations
“…presence of the protein is associated with more aggressive tumor behavior. For additional information in this respect, the interested reader may wish to consider previous reviews where such ideas have been discussed extensively [11,61]. A corollary to this concept is that Caveolin-1 function as a tumor suppressor is linked to events favoring cell death, while more aggressive tumor behavior is likely to be associated with Caveolin-1-dependent mechanisms that favor cell survival.…”
Section: )mentioning
confidence: 99%
“…Most notably, Caveolin-1 contains a tyrosine residue in position 14 that is phosphorylated in response to a large number of different stimuli. Often, but not always, non-receptor tyrosine kinases of the Src family are involved and phosphorylation is triggered as part of a so-called stress response [11]. The importance of Caveolin-1 in this context is underscored by the fact that Caveolin-1 knock-out mice display a remarkably reduced ability to regenerate specific tissues like the liver and also a dramatic decrease in life span [17][18].…”
Section: Introduction Caveolinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although further studies are needed to elucidate the precise functions of caveolin-1 in invadopodia formation, these findings imply that caveolin-1 plays multiple roles in the trafficking of invadopodia components. Clinical studies showed that the increased expression of caveolin-1 is correlated with the presence of metastasis and poor prognosis in several human cancers [28,29]. Taken together, blocking the functions of lipid rafts and caveolin-1 should be an approach to targeting invadopodia-mediated cancer cell invasion.…”
Section: Lipid Rafts and Caveolin-1 In Invadopodia Formationmentioning
confidence: 99%